2014
DOI: 10.3390/ijms150915426
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy via Activation of PI3K/Akt Pathway Contributes to the Protection of Ginsenoside Rb1 against Neuronal Death Caused by Ischemic Insults

Abstract: Lethal autophagy is a pathway leading to neuronal death caused by transient global ischemia. In this study, we examined the effect of Ginsenoside Rb1 (GRb1) on ischemia/reperfusion-induced autophagic neuronal death and investigated the role of PI3K/Akt. Ischemic neuronal death in vitro was induced by using oxygen glucose deprivation (OGD) in SH-SY5Y cells, and transient global ischemia was produced by using two vessels occlusion in rats. Cellular viability of SH-SY5Y cells was assessed by MTT assay, and CA1 ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 43 publications
4
63
0
Order By: Relevance
“…Similar result was found in human SH-SY5Y cells OGD model. In this model, activation of autophagy also relies on the PI3K/Akt/mTOR signaling pathway (Luo et al, 2014). Taken together, these studies strongly suggested that in neonatal hypoxia/ischaemia (HI) and primary cortical neurons OGC, rapamycin (mTOR) target axis could be a critical part of those integrated signalings which participate in the activation of autophagy.…”
Section: Autophagy Hypoxia and Mtormentioning
confidence: 80%
“…Similar result was found in human SH-SY5Y cells OGD model. In this model, activation of autophagy also relies on the PI3K/Akt/mTOR signaling pathway (Luo et al, 2014). Taken together, these studies strongly suggested that in neonatal hypoxia/ischaemia (HI) and primary cortical neurons OGC, rapamycin (mTOR) target axis could be a critical part of those integrated signalings which participate in the activation of autophagy.…”
Section: Autophagy Hypoxia and Mtormentioning
confidence: 80%
“…Thus it is likely that miR-145 exerted its cardioprotective effects through an increase in autophagy and activation of the Akt signaling axis. On the other hand, some previous studies revealed that Akt inhibited autophagy (5,15). However, this variation may have been due to differences in the cells, tissues, organs, and species studied.…”
Section: Signal Transductionmentioning
confidence: 77%
“…However in another study, Rg1 was demonstrated to reduce aldosterone-induced autophagy via the AMPK/mTOR pathway in NRK-52E cells [38]. Similarly, Rb1 was reported to have positive [39] and negative [40] effects on neuronal autophagy, respectively, in two different papers. Although the difference in cell types and observation indexes may contribute to these inconsistent results, further work is needed to identify the specific effects of gisenosides on autophagy and the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%